inx+in(x-6)=in(2x)

Simple and best practice solution for inx+in(x-6)=in(2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for inx+in(x-6)=in(2x) equation:


Simplifying
inx + in(x + -6) = in(2x)

Reorder the terms:
inx + in(-6 + x) = in(2x)
inx + (-6 * in + x * in) = in(2x)
inx + (-6in + inx) = in(2x)

Reorder the terms:
-6in + inx + inx = in(2x)

Combine like terms: inx + inx = 2inx
-6in + 2inx = in(2x)

Remove parenthesis around (2x)
-6in + 2inx = in * 2x

Reorder the terms for easier multiplication:
-6in + 2inx = 2in * x

Multiply in * x
-6in + 2inx = 2inx

Add '-2inx' to each side of the equation.
-6in + 2inx + -2inx = 2inx + -2inx

Combine like terms: 2inx + -2inx = 0
-6in + 0 = 2inx + -2inx
-6in = 2inx + -2inx

Combine like terms: 2inx + -2inx = 0
-6in = 0

Solving
-6in = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Divide each side by '-6'.
in = 0

Simplifying
in = 0

The solution to this equation could not be determined.

See similar equations:

| 8x-58=2*2+34 | | 8=8(1-6k) | | 1h=1 | | 6x+4x+6+4=38 | | -9+6w=5w | | a^2+1=29 | | 3(5y+2)-y=u+8 | | -92=4(-7x-2) | | 5x+55=9x-9 | | 2(3a+9)=20 | | 26p-4-11p=15p+6 | | 8x-4=4x+44 | | -6(4x+7)=78 | | -7p-39=5(-5p+3) | | -8(2x-2)=128 | | -14+4x-2x=30 | | P=A-ArT | | X^2+4y^2+6x+16y=11 | | 3x^26y-24=0 | | 10(9-x)= | | 35-(2c+3)=2(c-6)+c | | -7p-39=5(-5p+30) | | 3y+6x=360 | | 10x^2-17x+34=7x^2-26x+28 | | -15+-14e=-33 | | -13-8j=-5 | | 9m+6=96# | | 4b+6=-22 | | 4(p+5)=2 | | -43=13p-65 | | 0=x^4+4x^2-32 | | y=(-8)(1) |

Equations solver categories